The community structure of mangroves in Dao, Antique. - Wendam, Mary Hope Laserna
Mangrove forest are unique intertidal ecosystem that are primarily found on relatively sheltered coastlines, deltas, and lagoons in tropical and subtropical regions of the world. This study was conducted to assess the community structure of mangroves in Barangay Fatima, Barangay Igdalaguit, and Barangay Atabay, Dao, Antique, using the transect line method. Specifically, it aims to determine selected physical and chemical factors such as salinity, pH, temperature for water and soil as well as characterization of the substrate; identify and classify true mangrove species present in the area; and describe the community structure in terms of stand basal area, stems per hectare, relative density, relative frequency, relative dominance, importance value, Shannon index of diversity, zonation patterns, seedling and sapling density. No study has been done to document the commuity structure of mangroves in Dao, Antique thus this study was done to provide vital information needed for its proper management. Three stations were selected in Dao, Antique. Eight (8) species of true mangorves were identified belonging to six (6) families: Avicenniaceae - Avicennia alba, Avicennia marina; Combretaceae - Lumnitzera racemosa; Lythraceae - Pemphis acidula; Palmae - Nypa fruiticans; Rhizophoraceae - rhizophora mucronata, Rhizophora stylosa; and Sonneratiaceae - Sonneratia alba. The study area had a water salinity range of 22 ppt to 27.0 ppt; water temperature of 31 degrees centigrade in all stations; water pH of 8 for all stations; soil temperature range of 29 degrees centigrade to 31 degrees centigrade; and soil pH range of 6 to 8 . Basal area ranges from 0.49 m squared /ha. for Rhizophora mucronata to 279.826 m squared/ha. for Pemphis acidula. The species with the highest average of stems per hectarewas Avicennia marina with 20666 as well as the highest average density value of 133. Station 1 had the highest density and the lowest was Station 3. Rhizophora stylosa had the highest relative frequency of 25 percent occurrence. From the eight mangrove species recorded, Avicennia marina had the highest relative dominance of 136.720 and the least was Rhizophora mucronata with a relative dominance value of 0.006. The most important species was Avicennia marina with 285.720 and the least was Rhizophora mucronata with 3.237. the area is considered to be lowly diverse with 0.338 Shannon Index of Diversity. On the per plot basis of the Index of DiversityStation 1 had the highest with 0.644 and Station 3 had the least with 0.086. The srtucture of mangroves in this area is influenced by physico-chemical factors like substrate type (i.e. rocky, sandy, muddy); location and type of mangroves (i.e., narrow coastal fringing type) and human activities (i.e., reforestation, cutting, etc).